2007
DOI: 10.1186/bf03353111
|View full text |Cite
|
Sign up to set email alerts
|

Collisional disruption of weakly sintered porous targets at low-impact velocities

Abstract: Porous structure is common in the asteroids and satellites of the outer planets. In order to study the relationship between the structure of small bodies and their thermal and collisional evolution, we performed impact disruption experiments on porous sintered targets using a light-gas gun at velocities ranging from 10 to 100 m/s. The sintered glass bead targets were prepared to have roughly the same porosity but with different compressive strengths, ranging over an order of magnitude, by controlling sintering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…The energy density concept also leaves a possibility to compare to experiments dealing with other ranges for the parameters. For example Setoh et al (2007) report on collisional disruption of weakly sintered porous targets at impact speeds 10 times higher than ours, and particle densities 10 times higher, resulting in strength values 3 orders of magnitude higher, however, consistent with the our simple energy density model. Beitz et al (2011) performed impact experiments with cm-sized agglomerates consisting of spherical monodisperse SiO 2 grains and found catastrophic disruption from 2 m/s onward corresponding to an energy density of ≈1600 Pa for a volume filling factor of ≈ 0.4, close to the tensile strengths measured by Blum et al (2006) for such agglomerates.…”
Section: Constraints For the Strength From The Energy Densitysupporting
confidence: 90%
“…The energy density concept also leaves a possibility to compare to experiments dealing with other ranges for the parameters. For example Setoh et al (2007) report on collisional disruption of weakly sintered porous targets at impact speeds 10 times higher than ours, and particle densities 10 times higher, resulting in strength values 3 orders of magnitude higher, however, consistent with the our simple energy density model. Beitz et al (2011) performed impact experiments with cm-sized agglomerates consisting of spherical monodisperse SiO 2 grains and found catastrophic disruption from 2 m/s onward corresponding to an energy density of ≈1600 Pa for a volume filling factor of ≈ 0.4, close to the tensile strengths measured by Blum et al (2006) for such agglomerates.…”
Section: Constraints For the Strength From The Energy Densitysupporting
confidence: 90%
“…The measurements were performed using cylindrical samples cored from tea-cup shaped targets of diameter 1 cm and height 1.5 cm. In this new study, we revised the values of compressive strength of the four types weakest targets (1-A-1, 1-A-2, 1-B-1 and 1-B-2) used in the previous study (see Setoh et al, 2007b). The compressive strength ranges from 0.013 to 2.8 MPa.…”
Section: Targets Of Group 1: Tea Cupsmentioning
confidence: 96%
“…Although the impact strength of solid material increases almost monotonically with the static compressive strength, the impact strength of porous materials is scattered, although all the data points are above the line for the solid materials meaning that porous materials are stronger against impact disruption than solid materials as expected. Previous laboratory studies indicated that impact strength at lower velocity collision is lower than the one at higher velocity collision (e.g., Ryan et al 1991;Kawakami et al 1991;Setoh et al 2007). The two gypsum points are derived from the high (2850 -4170 m/s) and low (100 -758 m/s) velocity impact experiments of Kawakami et al (1991).…”
Section: -2 Crush Curvementioning
confidence: 99%